Modernization of the coolant temperature control system in steam generator sets - A. L. Lyashenko (Современная наука и инновации)
In the article the device and operation of steam unit as an example of the core of a nuclear reactor. The description of the equipment included in the multiple forced circulation circuit forming the reactor. Considered in detail the process of controlling the flow of coolant in the reactor fuel channels and the necessity of automation of the process. Formulated and solved the problem of synthesis of automatic control system. The possibility of using the device, extended frequency response for frequency analysis of distributed parameter systems. Formulated and solved the problem by developing a method for calculating the settings PID-controller.